2013
DOI: 10.1021/nn4035074
|View full text |Cite
|
Sign up to set email alerts
|

Design of Long Circulating Nontoxic Dendritic Polymers for the Removal of Iron in Vivo

Abstract: Patients requiring chronic red blood cell (RBC) transfusions for inherited or acquired anemias are at risk of developing transfusional iron overload, which may impact negatively on organ function and survival. Current iron chelators are suboptimal due to the inconvenient mode of administration and/or side effects. Herein, we report a strategy to engineer low molecular weight iron chelators with long circulation lifetime for the removal of excess iron in vivo using a multifunctional dendritic nanopolymer scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 43 publications
7
93
0
Order By: Relevance
“…This was first described by Hallaway et al, who achieved half-life extension up to 80 minutes and reduced toxicity after conjugating DFO to hydroxyl ethyl starch and dextran [5]. Similarly, we have previously shown that hyperbranched polyglycerol (HPG) conjugates of DFO with circulation half-life of 16 h was capable of efficiently removing iron from iron overloaded mice when treated every other day, demonstrating the proof-of-concept [20].…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…This was first described by Hallaway et al, who achieved half-life extension up to 80 minutes and reduced toxicity after conjugating DFO to hydroxyl ethyl starch and dextran [5]. Similarly, we have previously shown that hyperbranched polyglycerol (HPG) conjugates of DFO with circulation half-life of 16 h was capable of efficiently removing iron from iron overloaded mice when treated every other day, demonstrating the proof-of-concept [20].…”
Section: Introductionsupporting
confidence: 71%
“…ULC-DFO was obtained by conjugating DFO to HPG of different MW using reductive amination as previously reported [20]. In a typical reaction, 100-200 mg of HPG (25, 44 and 494 KDa) was dissolved in MilliQ water (2-4 mL).…”
Section: Synthesis Of Polymer Conjugatesmentioning
confidence: 99%
See 3 more Smart Citations